Structural Properties of Nickel Doped Cadmium Sulfide - B. Srinivasa Rao; B. Rajesh Kumar; G. Venkata Chalapathi; V. Rajagopal Reddy; T. Subba Rao (Журнал нано- та електронної фізики)
In the Present work, conventional chemical co-precipitation method was employed for the preparation of Nickel (2, 4, 6, 8 and 10 at % of Ni) doped CdS nanoparticles. The particle size and lattice parameters for each sample are determined from X-ray diffraction (XRD) analysis. From XRD patterns the broadening of the diffraction peaks indicates the nanostructure nature of the samples. Surface morphology of the samples was studied by Scanning Electron Microscope (SEM). Compositional Elemental analysis of data is obtained from Energy Dispersive Analysis of X-ray (EDAX) plots.